2012
DOI: 10.1111/j.1439-0418.2012.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of crimson clover dying mulch on two eggplant insect herbivores

Abstract: Eggplant Solanum melongena L., is often colonized by two early season insect defoliators. The Colorado potato beetle (CPB), Leptinotarsa decemlineata (Say), and flea beetles Epitrix spp., emerge from their overwintering sites in early spring and seek out emerging host plants such as eggplant. During the 2009 and 2010 growing season, field studies were conducted to investigate the impact of inter‐planting eggplant into a crimson clover (CC), Trifolium incarnatum L., winter cover crop on populations of flea beet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…In a study conducted by Hooks et al (2013a), despite significant reduction in pest density and greater proportions of beneficial arthropods, yields of eggplant inter-planted into a mowed crimson clover companion planting were significantly lower than in monoculture eggplant (Hooks et 2013b). In a subsequent study, when alternate rows of crimson clover were strip-tilled as opposed to mowed, pest suppression was maintained and eggplant growth and yield was significantly enhanced in crimson clover compared with monoculture unsprayed eggplant plantings (Hooks et al 2013b).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a study conducted by Hooks et al (2013a), despite significant reduction in pest density and greater proportions of beneficial arthropods, yields of eggplant inter-planted into a mowed crimson clover companion planting were significantly lower than in monoculture eggplant (Hooks et 2013b). In a subsequent study, when alternate rows of crimson clover were strip-tilled as opposed to mowed, pest suppression was maintained and eggplant growth and yield was significantly enhanced in crimson clover compared with monoculture unsprayed eggplant plantings (Hooks et al 2013b).…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, several studies have shown that the companion planting tactic can be effectively used to delay the onset of insect caused plant diseases and phytotoxemias in cucurbit crops (Frank & Liburd 2005;Nyoike et al 2008;Manandhar & Hooks 2011). Although companion plants have been found to reduce the occurrence of insect, disease and weed pests within cropping systems, they can compete with, and subsequently reduce, crop yields, thus making their use less practical (Vandermeer 1989;Walters & Young 2008;Hooks et al 2013a).…”
Section: Introductionmentioning
confidence: 98%
“…During both study years, significantly fewer CPB (adults, larvae and egg masses) were found on eggplant inter-planted into CC than in bare-ground (BG) eggplant plots; and although flea beetle abundance was greater in BG eggplant during year 2, they appeared to be less influenced by the presence of CC than were CPBs (Hooks et al 2012). These finding suggests that CC could be used to help manage CPB in eggplant.…”
Section: Introductionmentioning
confidence: 82%
“…Further, during sampling occasions this is consistently where flea beetles were found. The interest therefore was not to estimate or quantify the amount of damage throughout the whole plant, but to record the number of feeding pits displayed at the young terminal plant area during the early eggplant growth cycle when flea beetles were most abundant (Hooks et al 2012). Feeding injury was assessed weekly from 7 to 28 DAP.…”
Section: Plant Growth and Leaf Injury Measurementsmentioning
confidence: 99%
See 1 more Smart Citation